The Impact of Farmers' Socio-Economic Conditions Due to the Conversion of Agricultural Land in Setia Mulya Village, Bekasi Regency, Indonesia - Anastasia Rahmawati; Alwin Alwin; Agung Adiputra (Universitas Negeri Gorontalo, 2024)
Land conversion is the change of the original land function into another function. The conversion of laham affects the socio-economic conditions of farmers, especially in Setia Mulya Village. Socioeconomic conditions are a person's position in a community group that is determined by the type of economic activity, education, and income. The conversion of agricultural land can have an impact on the social and economic conditions of farmers. What is observed in this study is social conditions, economic conditions and their impact on farmers. The purpose of this study is to analyze changes in the socio-economic conditions of farmers due to land conversion and their impact on farmers' lives. The method used was a qualitative method with data sources obtained from observations, interviews, and documentation with farmers as respondents totaling 15 farmers, with sampling techniques using snowball sampling techniques. The results of the study showed changes in the socio-economic conditions of farmers due to land conversion that occurred in Setia Mulya Village. Changes in socio-economic conditions related to the age of farmers, changes in social status, changes in farmers' income, and farmers' household consumption. Farmers in Setia Mulya Village are cultivators so they have to pay rent to the landowner so that farming activities can continue. Although the area of agricultural land in Setia Mulya Village is very large, the high rental prices and the difficulty of irrigation flows make farmers have to look for decent agricultural land that can be used properly.